2014
DOI: 10.1364/oe.22.027968
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin circular polarization analyzer based on the metal rectangular split-ring resonators

Abstract: We propose an ultra-thin metasurface of the metal rectangular split-ring resonators (MRSRR) array which can modulate and analyze the wavefront of circularly polarized light efficiently. An incident circularly polarized light could be converted into the corresponding cross-polarized light which would be bent to ± 23° at a wavelength of 808 nm for the normal incidence. And a linearly polarized light would be decomposed into two lights of left and right-handed circular polarizations in the directions of ∓23° resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The transmitted light is RCP (LCP) for LCP (RCP) normal incidence which is accord with the nature of half-wave plate. Previous works have demonstrated that x-polarized light can be decomposed into two different circular polarization states of LCP and RCP, and the corresponding crosspolarized light deflect with opposite bending angles after passing through the metasurface [14,27]. Nevertheless, partial transmitted light (co-polarization) with same polarization as the incident light, (here is x-polarization), is also existence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmitted light is RCP (LCP) for LCP (RCP) normal incidence which is accord with the nature of half-wave plate. Previous works have demonstrated that x-polarized light can be decomposed into two different circular polarization states of LCP and RCP, and the corresponding crosspolarized light deflect with opposite bending angles after passing through the metasurface [14,27]. Nevertheless, partial transmitted light (co-polarization) with same polarization as the incident light, (here is x-polarization), is also existence.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being at its infancy, metasurfaces have exhibited great promise for wide applications and have been exploited for rotating polarization [8], engineering the optical spin-orbital interaction [9,10], creating optical vortex beams [11,12], coupling propagating waves to surface waves [13], creating ultra-thin circular polarization analyzer [14], fabricating polarization converters [15], biosensing applications [16], and so forth. Although great successes have been achieved, there are still several issues unsolved in the previous works.…”
Section: Introductionmentioning
confidence: 99%
“…And light propagation through the metasurfaces with linear phase discontinuities can be explained very well by the Generalized Snell's laws [22]. Metamaterials have opened a new door to manipulate intensity, phase distribution and polarization of light in nanoscale [21][22][23][24][25]. Therefore, the ultra-thin optical VPP composed of sub-wavelength metasurface is a potential candidate to generate vortex beams, which can be widely applied in the integrated optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation of SPPs results in a strong local enhancement of the electromagnetic field at the interface [1], and makes it possible to be focused into a strongly confined spot with size beyond the diffraction limit by appropriately designed plasmonic lens structures. Owing to the subwavelength scale feature and field enhancement effects of SPPs, they have attracted a variety of optical applications, such as probes of the scanning near-field optical microscopy [2], high-density optical data storage [3,4], analyzing circularly polarized lights [5][6][7][8][9], light focusing [10][11][12] and so on. At optical frequencies, planar focusing devices have been demonstrated by using arrays of nanoslits [13,14], nanoholes [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%